Prinsip Dan Unsur-Unsur Komunikasi Dalam Prespektif Al -Quran - Tomi Hendra; Peri Musliadi (Wardah, 2019)
Abstract: This study uses a type of library research (Library Research), namely by reading works related to the issues to be studied. The author will examine the principle of communication in the perspective of the Qur'an in terms of the elements of communication using the "(contenst analysis)" method (content analysis). The method "(contenst analysis)" is to analyze the principle of communication in the perspective of the Qur'an which is viewed from the elements of communication.The principle of communication in the Alquran describes that Qaulan Maysuran (words that are easy and proper), emphasize more on ethics and the message conveyed by communicators to communicants. A communicator in communication is required to be able to adjust himself to the state of the communicant and communicator must be able to convey a message that can be understood by the communicant, so that the communicant understands the message conveyed, namely an easy and appropriate message. Qaulan Ma'rufan (good words) emphasizes the ethics of communicators in conveying messages to communicants, so that communicants understand and do not have negative thoughts the message conveyed by communicators. Qaulan balighan (effective words), emphasizes the message conveyed by communicators. Because in this context a communicator communicates with a hard-hearted communicant or who is difficult to understand from the message conveyed or also the hypocritical communicant. Here a communicator must be able to convey a message that imprints on the heart of the communicant and advice that can make the heart of the communicant hard can soften, the message conveyed can also make a good effect of the communication process that occurs Keywords: Communication principles, communication elements